Labeling, agriculture and consumer: a reflection based on bibliometric tools - Figueroa-Rodríguez, Katia A.; Hernández Cabrera, Rocío L.; Figueroa Sandoval, Benjamín; Schwentesius Rindermann, Rita (Revista Mexicana de Ciencias Agrícolas, 2019)
The certifications seek to give a guarantee to the consumer, so agrifood producers have had to integrate this tendency to certify production, moving away from generic products towards a trend of differentiation. The objective of the research was to carry out an analysis using bibliometric tools on the subject of labeling, agriculture and consumer. A review of the topic was carried out from 1968 to 2018 (September 28), identifying 285 publications and conserving 204 useful documents, from which were analyzed: journals, countries and institutions that have published on the subject. The data was obtained from Scopus and analyzed with the VOSviewer program to determine the co-occurrence of terms and map the science. The results show that research is concentrated in three areas: the consumer, the agricultural producer and legislation. The issue of labeling is important for producers especially those who seek to be governed by aspects of ethical and ecological production; however, it is necessary to carry out communication campaigns to make the consumer aware of the certifications. In conclusion, the research on labeling, agricultural production and the consumer is in force, several studies are necessary that include the vision of the Mexican consumers or producers in order to be able to contribute to the scientific debate on this topic.
Keywords: certification; ecological; fair trad; legislation; organic agriculture